Efektivitas Penanganan Stunting Pada Balita di Puskesmas Kecamatan Bagan Sinembah Raya Kabupaten Rokan Hilir - Winda Elviana; Dedi Kusuma Habibie (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Stunting is failure to thrive in toddlers caused by chronic malnutrition so that children are too short for their age. Malnutrition occurs since the baby is in the womb in the early days after the baby is born however, stunting only appears after the baby is 2 years old. To tackle stunting, the government is aggressively making programs on stunting management. The government has given instructions to all groups, both from the government and the community, to help run the stunting management program, including the Bagan Sinembah Raya Subdistrict government, which has been the locus of stunting since 2021. The government and the Bagan Sinembah Raya District Health Center are working together in terms of stunting management in Bagan Sinembah District. Raya. The main problem is the high number of stunting cases caused by parenting styles and the lack of parental awareness of stunting. The purpose of this study was to determine the effectiveness of handling stunting in Bagan Sinembah Raya District. This study uses Theory from Budiani (2007) Effectiveness with indicators of Accuracy in Targeting, Program Socialization, Program Objectives, and Program Monitoring. This study used a qualitative research method with a descriptive approach, the required data such as primary and secondary data were obtained through a purposive sampling data collection technique used, namely literature study, interviews, documentation, and observation. The results of the study show that the implementation of stunting management with programs that have been implemented has not been effective. The inhibiting factors are that the program has not met the target, socialization is still lacking and also the facilities and infrastructure in running the program are still inadequate so that it becomes an obstacle in handling stunting in Bagan Sinembah Raya District.